Numerical study of nozzle diameter effect in fluid impingement cooling on cylindrical surface: article - Mohd Sabri, Nurul Farihin; Kamarrudin, Nadia (2020)
Jet impingement cooling method is an improved technique used to cool down the equipment and appliances in the industries and plants. This upgraded technique is replacing the old technique method by increasing the heat transfer rate and high efficiency. In this research, air was used as the cooling medium for cooling the equipment that have a curvature surface as most industrial equipment have a cylindrical shape. The objective of this study is to develop computational fluid dynamics model of jet impingement heat transfer on nozzle diameter effect towards curvature surface. The nozzle diameter B/D of 0.013, 0.027, 0.04, 0.053, 0.067 and 0.08 were used with constant Reynold number at 23700. The temperature of the water outlet of the jet is at 298.15 K and the heat flux q″ is at 5633 W/m2 . CFD simulation was run and using (k-Ԑ) turbulence model. The result is shown and calculated by using Navier-Stokes equation of energy, continuity and momentum equation. The numerical result shows that the turbulence kinetic energy is higher on the surface wall impingement at the larger diameter B/D = 0.08. This is due to the high momentum results from the high velocity gradient along the wall surface. The velocity increase with the increasing of the nozzle diameter which attributes to the higher Nusselt number and surface cooling rate.